Are manual therapy or booster sessions worthwhile in addition to exercise therapy for knee osteoarthritis: Economic evaluation and 2-year follow-up of a randomized controlled trial. (December 2021) - Pryymachenko, Yana; Wilson, Ross; Sharma, Saurab; Pathak, Anupa; Abbott, J. Haxby
Abstract: Background: Exercise therapy is known to be an effective intervention for patients with osteoarthritis, however the evidence is limited as to whether adding manual therapy or booster sessions are cost-effective strategies to extend the duration of benefits. Objective: To investigate the cost-effectiveness, at 2-year follow-up, of adding manual therapy and/or booster sessions to exercise therapy. Design: 2-by-2 factorial randomized controlled trial. Methods: Participants with knee osteoarthritis were randomly allocated (1:1:1:1) to: exercise therapy delivered in consecutive sessions within 9 weeks (control group), exercise therapy distributed over 1 year using booster sessions, exercise therapy plus manual therapy delivered within 9 weeks, and exercise therapy plus manual therapy with booster sessions. The primary outcome was incremental cost-effectiveness from health system and societal perspectives interpreted as incremental net monetary benefit (INMB). Results: Of 75 participants, 66 (88 %) were retained at 1-year and 40 (53 %) at 2-year follow-up. All three interventions were cost-effective from both the health system and societal perspectives (INMBs, at 0.5 × GDP/capita willingness to pay (WTP) threshold: $3278 (95%CI -3244 to 9800) and $3904 (95%CI -2823 to 10, 632) respectively for booster sessions; $2941 (95%CI -3686 to 9568) and $2618 (95%CI -4005 to 9241) for manual therapy; $270 (95%CI -6139 to 6679) and $404 (95%CI -6097 to 6905) for manual therapy with booster sessions). Conclusion: Manual therapy or booster sessions in addition to exercise therapy are cost-effective at 2-year follow-up. The evidence did not support combining both booster sessions and manual therapy in addition to exercise therapy. Highlights: Exercise therapy provides benefits for knee osteoarthritis. Manual therapy or booster sessions improve treatment effects and are cost-effective. More evidence is needed on the combination of manual therapy and booster sessions.